Staphylococcal peptidoglycans induce arthritis - Zai-Qing Liu; Guo‐Min Deng; Simon J. Foster; Andrej Tarkowski (2001)
Staphylococcus aureus is one of the most important pathogens in septic arthritis. To analyse the arthritogenic properties of staphylococcal peptidoglycan (PGN), highly purified PGN from S. aureus was intra-articularly injected into murine joints. The results demonstrate that PGN will trigger arthritis in a dose-dependent manner. A single injection of this compound leads to massive infiltration of predominantly macrophages and polymorphonuclear cells with occasional signs of cartilage and/or bone destruction, lasting for at least 14 days. Further studies showed that this condition is mediated by the combined impact of acquired and innate immune systems. Our results indicate that PGN exerts a central role in joint inflammation triggered by S. aureus.